Patient-derived organoids predict chemotherapy response of locally advanced gastric cancer - Miao Huang; Jiahui Chu; Wenbin Yu; Liliang Dou; Qiushi Wang; Fan Jiang; Meng Wei; Xiaohan Cui; Wen Zhao; Jianyuan Zhou; Song Li; Lian Liu (PLoS ONE, 2026)
The efficacy of standard adjuvant chemotherapy for locally advanced gastric cancer (GC) remains suboptimal, particularly in patients with signet-ring cell carcinoma (SRCC). Urgent demand exists for reliable preclinical models to predict therapeutic responses, and in vitro drug sensitivity testing using patient-derived organoids (PDOs) has emerged as a promising platform. In this study, PDOs were established from patients with locally advanced GC and analyzed via next-generation sequencing (NGS) and pharmacotyping. Seventeen GC PDOs were successfully generated, achieving a success rate of 63%. These PDOs closely recapitulated the histopathological and genetic features of their parental tumors. Drug sensitivity tests revealed subtype-specific response patterns: PDOs derived from SRCC were sensitive to epirubicin and paclitaxel but resistant to 5-fluorouracil (5-FU) and oxaliplatin. In contrast, non-SRCC PDOs demonstrated robust sensitivity to paclitaxel, epirubicin, and oxaliplatin. Among all tested drugs, paclitaxel showed the highest tumor-inhibitory efficacy in both subtypes. Furthermore, non-SRCC PDOs were significantly more sensitive to 5-FU and oxaliplatin than SRCC PDOs. Ex vivo pharmacotyping of PDOs accurately predicted clinical therapeutic responses in GC patients, with a sensitivity of 85.7%, specificity of 100%, and accuracy of 90.9%. Notably, patients whose PDOs were drug-sensitive in vitro had significantly longer disease-free survival than those whose PDOs were drug-resistant ( P = 0.044). These findings highlight the potential of GC PDOs as reliable preclinical models that faithfully recapitulate tumor biology and therapeutic responses, thereby providing a valuable tool for predicting individualized treatment outcomes and advancing precision oncology for GC.